High β-Glucans Oats for Healthy Wheat Breads: Physicochemical Properties of Dough and Breads - Astiz, Valentina (2022)
Bread is a highly consumed food whose nutritional value can be improved by adding an oat flour (Avena sativa L.-variety Bonaerense INTA Calen-Argentina) to a high-industrial quality wheat flour (Triticum aestivum L.). This cultivar of oat contains high amounts of β-glucans, which act as a prebiotic fiber. Wheat flour was complemented with different amounts of oat flour (5, 15, and 25%). A contribution of hydrophilic components from oat flour was evident in the oat–wheat mixtures. At the same time, the high content of total dietary fiber led to changes in the rheological properties of the dough. Mixtures with a higher proportion of oats showed an increase in alveographic tenacity (stiffer dough), higher stability, and a lower softening degree in farinographic assays. The dough showed significant increases in hardness and gumminess, without significant changes in cohesiveness, i.e., no disruption to the gluten network was observed. Relaxation tests showed that the blends with a higher oat content yielded 10 times higher stress values compared to wheat dough. Analysis of the oat–wheat breads showed improvements in nutritional parameters, with slight decreases in the volume and crust color. The crumb showed significant increases in firmness and chewing strength as the amount of oats added increased. Nutritional parameters showed that lipids, dietary fiber, and β-glucans were significantly increased by the addition of oats. Sensory analysis achieved high response rates with good-to-very good ratings on the hedonic scale set. Thus, the addition of oats did not generate rejection by the consumer and could be accepted by them. Breads with wheat and oats showed nutritional improvements with respect to wheat bread, since they have higher dietary fiber content, especially in β-glucans, so they could be considered functional breads.